Observations of tropospheric aerosols and NO2 in Hong Kong over 5years using ground based MAX-DOAS - Chan, Ka Lok; Wiegner, Matthias E.; Wenig, Mark; Pöhler, Denis (The science of the total environment, 2018)
In this paper, we present long term observations of atmospheric aerosols and nitrogen dioxide (NO2) in Hong Kong using a Multi-AXis Differential Optical Absorption Spectroscopy (MAX-DOAS) instrument. Ground based MAX-DOAS measurements were performed over 5years from December 2010 to November 2015. Vertical distribution profiles of aerosols and NO2 were derived from MAX-DOAS O4 and NO2 observations by applying the optimal estimation method. Retrieved MAX-DOAS measurements of aerosols and NO2 show good agreement with sun photometer observation of aerosol optical depths (AODs) and long path DOAS measurement of ground level NO2 mixing ratios. Tropospheric vertical column densities (VCDs) of NO2 derived from MAX-DOAS measurements are used to validate OMI satellite NO2 observations. Daily data show reasonably good agreement with each other with Pearson correlation coefficient R=0.7. However, MAX-DOAS NO2 VCDs are on average higher than OMI observations by a factor of 2. Introducing aerosols in the air mass factor calculation would enhance the OMI VCDs by 7-13%, the remaining discrepancy is mainly due to the differences in spatial coverage between the two instruments. Diurnal variation patterns of aerosols and NO2 indicated significant contributions from local anthropogenic emissions. Analysis of air mass transport shows that the enhancement of surface aerosols and NO2 concentrations mainly results from accumulation of local emissions under low wind speed conditions.